The role and functions of building audit for goverment buildings / Nor Asma Abdullah - Abdullah, Nor Asma (Faculty of Architecture, Planning and Surveying, 2008)
It is well known that the asset facility manager is allowed to get on and implement the maintenance strategy and develop the operation without let or hindrance is an endangered species - external influences can cause even the best laid plans to go astray. Occasionally it is essential for the facility manager to take a step back and look at the overall progress being made; in short to carry out a building audit. An audit is a more questioning activity than monitoring performance indicators. The process includes facilities audits, utility audits, state controlled maintenance, and building maintenance. Services include setting priorities of building deficiencies, cost estimates for repairs, and development and maintenance of facilities condition inventories database.